2012
DOI: 10.1063/1.4768844
|View full text |Cite
|
Sign up to set email alerts
|

Transport in graphene antidot barriers and tunneling devices

Abstract: Periodic arrays of antidots, i.e. nanoscale perforations, in graphene enable tight confinement of carriers and efficient transport barriers. Such barriers evade the Klein tunneling mechanism by being of the mass rather than electrostatic type. While all graphene antidot lattices (GALs) may support directional barriers, we show, however, that a full transport gap exists only for certain orientations of the GAL. Moreover, we assess the applicability of gapped graphene and the Dirac continuum approach as simplifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…A major issue is the deterioration of the graphene sheet quality and the difficulty in maintaining a uniform size and separation of antidots throughout the lattice. Indeed, the band-gap behavior predicted for certain lattice geometries [23,24,[38][39][40][41][42][43][44][45] is particularly sensitive to small levels of geometric disorder, which may not be possible to eliminate in experiment [46][47][48][49][50][51]. Although such uniformity is not an essential ingredient for commensurability oscillations, invasive etching processes usually reduce the mean free path significantly so that electrons are principally scattered by defects and not antidots, thus suppressing commensurability effects.…”
Section: Introductionmentioning
confidence: 99%
“…A major issue is the deterioration of the graphene sheet quality and the difficulty in maintaining a uniform size and separation of antidots throughout the lattice. Indeed, the band-gap behavior predicted for certain lattice geometries [23,24,[38][39][40][41][42][43][44][45] is particularly sensitive to small levels of geometric disorder, which may not be possible to eliminate in experiment [46][47][48][49][50][51]. Although such uniformity is not an essential ingredient for commensurability oscillations, invasive etching processes usually reduce the mean free path significantly so that electrons are principally scattered by defects and not antidots, thus suppressing commensurability effects.…”
Section: Introductionmentioning
confidence: 99%
“…GALs have tunable band gaps that depend on geometric factors 20,21 , which make them interesting for electronic and optoelectronic applications. It has been shown that a narrow slice of GAL with just a few rows connected to graphene sheets on either side is sufficient to block electron transport in the energy gap of the GAL 22,23 . By omitting antidots in some regions of such a GAL barrier, electrons can be guided through the unpatterned part, giving rise to an electronic waveguide 24 , reminiscent of a photonic waveguide in a photonic crystal.…”
Section: Introductionmentioning
confidence: 99%
“…In our transport calculations, we use the Landauer-Büttiker formalism with a tight-binding model, which is widely used for calculating the quantum transport in nanoscale devices [31][32][33][34][35][36][37][38][39]. The magnetic field is included in the Hamiltonian by a Peierls substitution.…”
Section: Introductionmentioning
confidence: 99%